InGaN light-emitting diodes with oblique sidewall facets formed by selective growth on SiO₂ patterned GaN film - Sheu, Jinn-Kong; Chang, Kuo-Hua; Tu, Shang-Ju; Lee, Ming-Lun; Yang, Chih-Ciao; Hsu, Che-Kang; Lai, Wei-Chih (Optics express, 2010)
In this study, GaN-based light-emitting diodes (LEDs) with naturally formed oblique sidewall facets (OSFs) were fabricated through a selective regrowth process. The SiO₂ mask layer was patterned on a heavily doped n-GaN template layer rather than on a sapphire substrate. As a result, the periphery of the LED included several OSFs around the regrown GaN mesa. While processing the device, dry etching was unnecessary for exposing the n-GaN underlying layer in order to form the n-type Ohmic contacts. This could be attributed to the fact that the n-GaN template layer with an electron concentration of around 8 × 10¹⁸/cm³ was exposed after the removal of the SiO₂ mask layer. With an injection current of 20 mA, GaN-based LEDs with OSFs exhibited a 21% enhancement in light output compared with those that have vertical sidewall facets. The enhancement is attributed to the fact that photons extracted from OSFs can reduce internal absorption loss.